2013
DOI: 10.1002/cbic.201300525
|View full text |Cite
|
Sign up to set email alerts
|

The Effect of the Length of Histone H3K4me3 on Recognition by Reader Proteins

Abstract: Thermodynamic analyses of associations between reader domain proteins and histone H3K4me3 peptides demonstrated that the shortest recognised histone substrate contains just the first four amino acids in histone 3. Deletion or addition at the N terminus resulted in a substantial decrease of binding affinity for most readers, thus verifying the importance of the H3A1 binding pocket.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

5
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

4
2

Authors

Journals

citations
Cited by 8 publications
(18 citation statements)
references
References 22 publications
5
13
0
Order By: Relevance
“…dissociation constant K d , free energy of binding Δ G °, enthalpy of binding Δ H °, and entropy of binding -TΔ S °) for the association of reader-histone complexes ( Table 2 , Fig 4 ). Consistent with previous studies, thermodynamics of interactions between H3K4me3 and Sgf29 showed that the association is enthalpy-driven (Δ H ° = -8.1 kcal mol -1 ), whereas the entropy of binding is slightly unfavorable (-TΔ S ° = 0.6 kcal mol -1 )[ 12 ]. H3K4me2 histone peptide exhibits slightly lower binding affinity than H3K4me3 for binding to WT Sgf29 ( K d = 4.7 μM for H3K4me2 vs. 3.1 μM for H3K4me3).…”
Section: Resultssupporting
confidence: 89%
See 3 more Smart Citations
“…dissociation constant K d , free energy of binding Δ G °, enthalpy of binding Δ H °, and entropy of binding -TΔ S °) for the association of reader-histone complexes ( Table 2 , Fig 4 ). Consistent with previous studies, thermodynamics of interactions between H3K4me3 and Sgf29 showed that the association is enthalpy-driven (Δ H ° = -8.1 kcal mol -1 ), whereas the entropy of binding is slightly unfavorable (-TΔ S ° = 0.6 kcal mol -1 )[ 12 ]. H3K4me2 histone peptide exhibits slightly lower binding affinity than H3K4me3 for binding to WT Sgf29 ( K d = 4.7 μM for H3K4me2 vs. 3.1 μM for H3K4me3).…”
Section: Resultssupporting
confidence: 89%
“…We furthermore showed that H-bonding between Y245 and backbone K4 amide provides an additional driving force (~1 kcal mol -1 ) for the specific readout of H3K4me2/3 by Sgf29. This work, together with our previous studies that confirmed the existence of the H3A1 recognition site,[ 12 ] highlights the importance of electrostatic interactions and hydrogen bonding in specific recognition of H3K4me2/3 by the Sgf29 tandem tudor domain.…”
Section: Discussionsupporting
confidence: 77%
See 2 more Smart Citations
“…Studies on the related protein systems showed that Trp forms significantly stronger cation– π interactions with quaternary ammonium ions than do Phe or Tyr residues 24 25 . For SGF29, the electrostatic interactions between Kme3 and D266, and between the positively charged α-amino group of A1 and the H3A1 binding pocket importantly contribute to the overall binding affinity of H3K4me3 (refs 22 , 33 ).…”
Section: Resultsmentioning
confidence: 99%